The Intertextuality of the Protsyuk’s Novel “Totem” (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article is devoted to the analysis of intertextual markers in S. Protsyuk’s novel “Totem”, stated in its own textual and paratextual relations. The most numerous in the intertextual dimension of the work are allusions. A special intertextual aura of S. Protsyuk’s novel “Totem” is produced by those with whom persistent associations are associated as certain psychocodes. The characters’ names execute meaningful load (Mary, Victor). Important intertextual sounding in the novel is added by Biblicalism, scripture quotes, and the image of Christ the Savior, who set ready text precedents for authorial reflections and artistic parallelism, responsible for shaping the discourse of salvation, insight, and conversion. In contrast to the God-centered intertextual line of the work in S. Protsyuk’s novel “Totem” a number of destructive images, serving as serious psychological destructions, were used, expressing the motive of human degradation, sin, lust, immorality, and pathologic behaviors and behavioral models - Maodzeduna, Caligula, Nefertiti with the characters of the novel; Victor’s and his father’s perversity, lust, and adventurism are paralleled by the vital postulates of Don Juan, Casanova and love-lovers. Special intertextual sound in the novel of S. Protsyuk acquires the metaphor of Joseph Mengele as an allusion to the prototype of a cruel experimenter, which leads to totem dependence / totemolinking, associated with human destruction, degeneration, delusionalness, sinlessness, immorality. The allusion to Joseph Mengele in the novel motivates the appearance of numerous human flaws, expresses the motive of sin and apostasy, explains the psychological codes of a number of neuroses, psychoses, fears, pathologies in the lives of heroes. Intertextual markers in S. Protsyuk’s novel “Totem” are epigraphs to separate sections of the work, expressing the author’s position and consonance with the cited, noting the pre-emptive nature of informing plot collisions.
Keywords: intertextuality; paratextuality; allusion; epigraph; destruction; psychological code